2021
DOI: 10.1093/molehr/gaab044
|View full text |Cite
|
Sign up to set email alerts
|

Increased miR-6875-5p inhibits plasmacytoid dendritic cell differentiation via the STAT3/E2-2 pathway in recurrent spontaneous abortion

Abstract: Recurrent spontaneous abortion (RSA) is a common complication of early pregnancy. Dendritic cells (DCs) are thought to confer fetal-maternal immunotolerance and play a crucial role in ensuring a successful pregnancy. A decrease of plasmacytoid dendritic cells (pDCs) was found to be involved in RSA, but the underlying mechanisms of decreased pDC in RSA remain unclear. MicroRNAs (miRNAs) play critical roles in RSA as well as the development, differentiation and functional regulation of pDCs; however, the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Impaired STAT3 expression is a possible cause of altered endometrial receptivity and decidualization via different pathways [ 49 , 50 , 51 , 52 , 53 , 54 ]. Both STAT3 and TCF4 are downregulated in the decidua of patients with recurrent spontaneous abortion compared with those with normal pregnancy [ 55 ]. In a mouse model, an impaired LIF/STAT3 pathway resulted in the failure of decidualization and embryo implantation [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired STAT3 expression is a possible cause of altered endometrial receptivity and decidualization via different pathways [ 49 , 50 , 51 , 52 , 53 , 54 ]. Both STAT3 and TCF4 are downregulated in the decidua of patients with recurrent spontaneous abortion compared with those with normal pregnancy [ 55 ]. In a mouse model, an impaired LIF/STAT3 pathway resulted in the failure of decidualization and embryo implantation [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…RSA results from impaired trophoblast function, and further study has shown that STAT3 expression could a ect trophoblast cell proliferation and migration [41]. Existing studies have con rmed that the reduction of plasmacytoid dendritic cells in RSA could be mediated by the regulation of STAT3 expression [42]. STAT3 signaling has been veri ed to exert anti-in ammatory IL-10 expression in decidua cells to protect pregnancy [43].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated thatupregulated miR-365 in the decidua of RSA patients compared to that of normal pregnant women could cause DCs apoptosis throughsuppressing serum and glucocorticoid-regulated kinase-1, which may be a potential underlying mechanism of early RSA [37] . Our recent research demonstrated increased miR-6875-5p in plasmacytoid DCs of RSA patients inhibited the cell differentiation via the STAT3/transcription factor 4 ( Tcf4/E2-2 ) signaling [38] . Additionally, a study distinguished 32 upregulated miRNAs in the decidua of RSA patients compared to normal pregnant women through deep sequencing; Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses predicted that these miRNAs are mainly involved in the regulation of trophoblast cells apoptosis and death [39] .…”
Section: Mirnas Lncrnas and Circrnas In Pregnancy-associated Diseasesmentioning
confidence: 95%